CHILDREN'S ARTERIAL HYPERTENSION: DRUG CHOICE. THE RESULTS OF THE PHARMACOEPIDEMIOLOGICAL STUDY RIFAGD - L.P. Zharkova; L.V. Kozlova; V.I. Makarova; N.L. Izbenko; O.I. Chirkova; E.I. Temnikova; L.P. Parmenova; M.K. Soboleva; Zh.V. Nefedova; A.L. Barsuk; M.L. Ogneva; L.A. Silverstova; et al. (Педиатрическая фармакология)
The multicentered pharmacoepidemiological study «Rifagd» (prevalence and pharmacotherapy of arterial hypertension in children) in 13 cities of Russia was conducted with the purpose of analyzing of pediatricians' approach to the treatment of children's arterial hypertension, including drug choice. This allowed to estimate their experience, knowledge, as well as to direct the way to improvements of quality in medical treatment of patients with arterial hypertension. The majority of pediatricians (83,1%) encounter difficulties in hypertension treatment in connection with guidelines absence (37,3%), medical practice absence (30,4%) and «absence of indications for the application of antihypertensive drugs in pediatrics» (31,9%). for arterial hypertension treatment pediatricians use AgE-inhibitors, diuretics and beta blockers.Key words: rifagd, arterial hypertension, pharmacoepidemiology, questioning of pediatricians, ace inhibitors, diuretics, beta blockers.